A GIS-Based Review of Ancient Chinese Port Cities and the Silk Road: Applications and Challenges of Historical Map Digitization - Zheng, Kaiwen (Transactions on Environment, Energy and Earth Sciences, 2024)
This essay explores the application of Geographic Information Systems (GIS) in the study of ancient Chinese port cities along the Silk Road. It highlights the significance of these cities as strategic nodes facilitating trade and cultural exchange. The digitization of historical maps using GIS technologies allows for detailed spatial analysis, modeling environmental changes, and understanding the urban evolution of these port cities. Challenges such as map accuracy, preservation issues, and cross-temporal data integration are discussed. The study emphasizes the potential of GIS in historical research despite these challenges.